2016
DOI: 10.1002/hyp.10848
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of groundwater dynamics and streamflow response from different hydropedological units in a montane catchment

Abstract: Groundwater dynamics play an important role in runoff generation and hydrologic connectivity between hillslopes and streams. We monitored a network of 14 shallow groundwater (GW)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 70 publications
3
57
0
2
Order By: Relevance
“…In periods of extreme wetness, such as in December 2015 and January 2016, overland flow and/or shallow lateral subsurface storm flow may occur when the surface soil horizons saturate and the hillslopes become hydrologically connected to the stream channel network (Devito, Hill, & Roulet, ; Tromp‐van Meerveld & McDonnell, ; Tunaley, Tetzlaff, Lessels, & Soulsby, ). In contrast, during drier periods with lower water tables, groundwater seepage routes water slowly downslope towards the valley bottom; this is then partitioned with some exfiltrating at the edge of the saturated area and some draining deeper into the drift, much of which eventually discharges to the stream (Ala‐aho et al, ; Blumstock et al, ; Haria & Shand, ; Masaoka, Kosugi, Yamakawa, & Tsutsumi, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In periods of extreme wetness, such as in December 2015 and January 2016, overland flow and/or shallow lateral subsurface storm flow may occur when the surface soil horizons saturate and the hillslopes become hydrologically connected to the stream channel network (Devito, Hill, & Roulet, ; Tromp‐van Meerveld & McDonnell, ; Tunaley, Tetzlaff, Lessels, & Soulsby, ). In contrast, during drier periods with lower water tables, groundwater seepage routes water slowly downslope towards the valley bottom; this is then partitioned with some exfiltrating at the edge of the saturated area and some draining deeper into the drift, much of which eventually discharges to the stream (Ala‐aho et al, ; Blumstock et al, ; Haria & Shand, ; Masaoka, Kosugi, Yamakawa, & Tsutsumi, ).…”
Section: Discussionmentioning
confidence: 99%
“…A core groundwater monitoring programme in the catchment has been focused around a hillslope transect where boreholes monitor water table fluctuations in the upper drift in the main landscape positions (Figures ). Previous work has shown that this gives a broadly representative insight into water table levels over the wider catchment (Blumstock et al, ). Between August 2015 and September 2016, we monitored water levels in four (>1.8 m) wells (deep wells [DW]) along the hillslope transect (cf Figure ), from the valley bottom up to the hillslope top (north to south).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the entire study period, the residual rainfall (46.7%) after ET loss percolated into the deeper soils, because surface runoff is negligible at the study plot due to the flat terrain and permeable podzolic soils (Tetzlaff et al, ). Based on previous studies using geophysical surveys (Soulsby et al, ) and a tracer‐aided model (Birkel, Soulsby, & Tetzlaff, ), most of the excess rainfall beyond ET becomes storage in soils; then may later recharge groundwater (Tetzlaff et al, ), and contribute to downslope riparian zones and streams through subsurface lateral flow (Blumstock, Tetzlaff, Dick, Nuetzmann, & Soulsby, ). The MEP‐derived water balance highlights the qualitative and quantitative effects of vegetation on water partitioning and storage in heather dominated areas such as the study site.…”
Section: Discussionmentioning
confidence: 99%